2017
DOI: 10.1590/1413-785220172504160652
|View full text |Cite
|
Sign up to set email alerts
|

Postural Control Assessment in Physically Active and Sedentary Individuals With Paraplegia

Abstract: Objective: The aim of this study was to evaluate functional independence and trunk control during maximum-range tasks in individuals with spinal cord injuries, who were divided into sedentary (SSI, n=10) and physically active (PASI, n=10) groups . Methods: Anamnesis was conducted and level and type of injury were identified (according to the American Spinal Injury Association protocol, ASIA) and the Functional Independence Measure (FIM) questionnaire was applied. For the forward and lateral reach task, the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
4
0
1
Order By: Relevance
“…Improvements in selfesteem, QoL, and fitness levels have been reported following community exercise programs in individuals with SCI. 16,17,27,28,[30][31][32] This study revealed a statistically significant increase in QoL, as demonstrated by the LiSAT-9 outcome measure. Garshick et al found a similar positive association between prescribed exercise programs and a higher satisfaction of life for individuals with SCI.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Improvements in selfesteem, QoL, and fitness levels have been reported following community exercise programs in individuals with SCI. 16,17,27,28,[30][31][32] This study revealed a statistically significant increase in QoL, as demonstrated by the LiSAT-9 outcome measure. Garshick et al found a similar positive association between prescribed exercise programs and a higher satisfaction of life for individuals with SCI.…”
Section: Discussionsupporting
confidence: 63%
“…The program volunteers took the measurement from the distal end of the third metacarpal along a wall-mounted yardstick placed at the height of the acromion of the participant's dominant extremity. 25,27 Measurements were reported in centimeters. The mFRT is a reliable outcome measure for measuring forward reach and sitting balance in persons with SCI who are unable to stand.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The strength of shoulder flexor, extensor, abductor, internal and external rotator muscles and elbow flexor muscles were measured with a Lafayette (Pelican 1150 Case, Pelican Products, Torrance, CA USA) myometer device (Livingston et al, 2015). Modified Functional Reach Test for evaluating the trunk balance was applied in 3 different versions including unilateral, bilateral and lateral reach (Magnani et al, 2017).…”
Section: Measurementsmentioning
confidence: 99%